THE RELATIONSHIP OF THE DEVELOPMENT OF FORMS OF SOCIAL CONSCIOUSNESS WITH SPIRITUALITY - Rakhmonova Gulzoda Ganievna (Western European Studies, 2024)
This article reveals that the development of the whole requires the development of the part. The importance of the development of forms of social consciousness in the development of spirituality in society is justified by various examples.
Keywords: Gathering; hunting; animal husbandry; farming